Radiosynthesis of α-[18F]Fluoroamides with [18F]AgF - Gong, Kehao; Yin, Zhengxu; Song, Pengfei; Xu, Bo; Han, Junbin (Synlett, 2024)
A silver-promoted nucleophilic radiofluorination of α-bromoamides has been developed for the radiosynthesis of α-[18F]fluoroamides. The reaction conditions are straightforward and compatible with primary, secondary, and tertiary α-bromoamides. Furthermore, the methodology has been successfully applied to the synthesis of bioactive radiotracers with good radiochemical conversion (RCC) and radiochemical yield (RCY).
Keywords: silver; radiofluorination; α-bromoamides; α-[18F]fluoroamides; nucleophilic reactions